Sexual anarchy or civilized eros? : New sexual parameters, family and monogamy among evangelical gay men - Lacerda Coelho, Carlos (Latitude, 2024)
The fatalistic discourse that we are moving towards a world without rules, whose most primitive instincts are reshaping life in contemporary societies, is strongly present, among conservative segments, in the social fabric. Such a narrative is constantly exploited by fundamentalist religious sectors, especially when they use the moral panic around issues related to the field of dissident sexualities from the heterosexual norm. Evidence has pointed to the reverse. In the field of sexual morality, especially related to sexual minorities, the phenomenon of inclusive churches indicates clear evidence of the reconfiguration of a sexual ethic, adapted to the reality of the LGBTI+ population. The article aims to discuss, based on investigations carried out through field research, during some years in inclusive churches in the city of Maceió (AL), the reconfiguration of the notion of “sin of homosexuality”, arising from the hegemonic Christian discourse, as well as the importance given to the notions of monogamous marriage, fidelity, codes of holiness and purity as guides for the action of LGBTI+ evangelicals in the spaces of the temple and society as a whole. It is possible to point out, in agreement with Gilles Lipovetsky, that the growth of individual autonomy did not lead to the decay of collective life. Nor has cultural liberalism fostered a sexuality without rules.Keywords: Homosexuality. Christianity. Moralities. Inclusive Churches.